The grounded theory of “trust building” - Ramezani, Monir (Nursing ethics, 2019)
Background:Despite the growing importance of spiritual care, the delivery of spiritual care is still an area of disagreement among healthcare providers.Objective:To develop a grounded theory about spiritual care delivery based on Iranian nurses’ perceptions and experiences.A grounded theory approach:A qualitative study using the grounded theory approach.Participants and research context:Data were collected through holding 27 interviews with 25 participants (17 staff nurses, 3 physicians, 3 patients, 1 family member, and 1 nurse assistant). The study setting was the Imam Khomeini Hospital Complex. Sampling was started purposively and continued theoretically. Data analysis was performed by the method proposed by Strauss and Corbin.Ethical consideration:The study was approved by the Ethics Committee of Tarbiat Modares University and the agreement of the administrators of the study setting was got before starting the study.Results:The core category of the study was “Trust building” which reflected the nature of spiritual care delivery by nurses. Trust building was the result of eight main categories or strategies including creating a positive mentality at hospital admission, understanding patients in care circumstances, having a caring presence, adhering to care ethics, developing meaningful relationships, promoting positive thinking and energy, establishing effective communication with patients, and attempting to create a safe therapeutic environment. Poor interprofessional coordination negatively affected this process while living toward developing greater cognizance of divinity and adhering to the principles of professional ethics facilitated it. The outcome of the process was to gain a sense of partial psychological security.Conclusion:The “Trust building” theory can be used as a guide for describing and expanding nurses’ roles in spiritual care delivery, developing care documentation systems and clinical guidelines, and planning educational programs for nursing students and staff nurses.